PENGARUH EKUITAS MEREK ( BRAND EQUITY ) TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE OPPO (STUDI KASUS PADA MASYARAKAT KOTA BIMA) - Leni Marlina; Ismunandar Ismunandar (Jurnal Bina Bangsa Ekonomika, 2021)
This research aims to find out the influence of brand equity variables on oppo smartphone purchase decisions on the people of Bima City. This type of research is associative, the research instrument used is a likert-scale questionnaire. The population in this study is the entire community of Bima City who have bought Oppo smartphone products whose numbers are not known with certainty (unknowns population). The sample in this study was as many as 50 respondents using the unknown population formula, a sampling technique used that is purposive sampling. The data collection techniques used in this study are observations, questionnaires and library studies. The data analysis techniques used are validity test, reliabiity test, simple linear regression analysis, simple correlation coenphysien, determination coefficient and t test. Based on the results of analysis and hypothesis testing states that there is an influence of Brand Equity on Oppo Smartphone Purchase Decisions (case studies in the people of Bima City) with a moderate level of relationship intensity and a magnitude of influence of 30.8%.